The Influence of the Flipped Classroom Learning Model Flipbook Media Assistance for Financial Literacy in Elementary School Students - Wulan Novitasari; Angga Setiawan; Indah Yunitasari (Universitas Islam Balitar, 2025)
Financial literacy is an important skill that needs to be possessed from an early age, including in elementary school students. This literacy includes understanding, managing, and making decisions related to finance. The results of observations at SDN 1 Karangsoko, SDN 1 Ngares, and SDN 3 Karangsoko showed that students still had difficulty understanding the concept of financial literacy, and teachers had not integrated it optimally into the learning process. This study aims to determine the effect of the flipped classroom learning model assisted by flipbook media on the financial literacy of fourth grade elementary school students. The method used is quantitative with a quasi-experimental design of the nonequivalent control group design type , involving the experimental class and the control class. The sampling technique used purposive sampling . The data collection instruments were multiple choice and descriptive tests, and data analysis used an independent sample t-test . The results showed that there was a significant difference between the financial literacy skills of students who learned using the flipped classroom model assisted by flipbook media compared to conventional learning, with a significance value of 0.000 <0.05. The flipped classroom model assisted by flipbook media has proven to be effective in improving students' financial literacy. This study recommends the application of this model in learning and suggests the use of flipbook media as an innovation to improve students' financial literacy skills in elementary schools.